Rosemary, heather and heterofloral honeys protect towards cytotoxicity of acrylamide in human hepatoma cells - Haza, Ana Isabel; Mademtzoglou, Despoina; Coto, Angel Luis; Morales, Paloma (Revista Complutense de Ciencias Veterinarias, 2010)
In April 2002 the Swedish Agency for Food Safety alerts of the presence of acrylamide (AA) in carbohydrate-rich foodstuffs subjected to elevated frying temperatures (150 - 180°C) such as fried potatoes, biscuits or breakfast cereals. The International Agency on Research on Cancer (IARC) classified acrylamide as a probable carcinogen, Group 2A. In consequence, one of the priority objectives of Food Safety is to reduce the presence of this substance in food. Numerous studies show the inhibitory effect of antioxidants present in fruit and vegetable extracts against the formation of acrylamide. Honey is also a good source of antioxidants since it contains a great variety of phenolic compounds. Therefore the main objective of this work was to evaluate the protective effect of three Madrid honeys of different floral origin against the AA-induced cytotoxicity in human hepatoma cells (HepG2). The results showed that the acrylamide in concentrations 1.4 and 2.8 mg/ml and in a 24-hour incubation period significantly reduced the percentage of cell viability (67 and 24 %, respectively). In simultaneous treatment of acrylamide (2.8 mg/ml) and the corresponding honeys we noted that rosemary honey in all concentrations tested increased the percentage of cell survival in 40-49 %, while heather honey and heterofloral honey increased cell viability by 54 and 66% respectively. The artificial honey did not mitigate the AA-induced cytotoxic effect. As a result, the protective effect of the evaluated honeys can be attributed to its polyphenolic content and not the sugar constituents.